Identification of a Gal/GalNAc Lectin in the Protozoan Hartmannella vermiformis as a Potential Receptor for Attachment and Invasion by the Legionnaires' Disease Bacterium - Venkataraman, Chandrasekar (The Rockefeller University Press, 1997)
The Legionnaire's disease bacterium, Legionella pneumophila, is a facultative intracellular pathogen which invades and replicates within two evolutionarily distant hosts, free-living protozoa and mammalian cells. Invasion and intracellular replication within protozoa are thought to be major factors in the transmission of Legionnaire's disease. Although attachment and invasion of human macrophages by L. pneumophila is mediated in part by the complement receptors CR1 and CR3, the protozoan receptor involved in bacterial attachment and invasion has not been identified. To define the molecular events involved in invasion of protozoa by L. pneumophila, we examined the role of protein tyrosine phosphorylation of the protozoan host Hartmannella vermiformis upon attachment and invasion by L. pneumophila. Bacterial attachment and invasion were associated with a time-dependent tyrosine dephosphorylation of multiple host cell proteins. This host cell response was highly specific for live L. pneumophila, required contact with viable bacteria, and was completely reversible following washing off the bacteria from the host cell surface. Tyrosine dephosphorylation of host proteins was blocked by a tyrosine phosphatase inhibitor but not by tyrosine kinase inhibitors. One of the tyrosine dephosphorylated proteins was identified as the 170-kD galactose/N-acetylgalactosamine–inhibitable lectin (Gal/GalNAc) using immunoprecipitation and immunoblotting by antibodies generated against the Gal/GalNAc lectin of the protozoan Entamoeba histolytica. This Gal/GalNAc–inhibitable lectin has been shown previously to mediate adherence of E. histolytica to mammalian epithelial cells. Uptake of L. pneumophila by H. vermiformis was specifically inhibited by two monovalent sugars, Gal and GalNAc, and by mABs generated against the 170-kD lectin of E. histolytica. Interestingly, inhibition of invasion by Gal and GalNAc was associated with inhibition of bacterial-induced tyrosine dephosphorylation of H. vermiformis proteins. High stringency DNA hybridization confirmed the presence of the 170-kD lectin gene in H. vermiformis. We conclude that attachment of L. pneumophila to the H. vermiformis 170-kD lectin is required for invasion and is associated with tyrosine dephosphorylation of the Gal lectin and other host proteins. This is the first demonstration of a potential receptor used by L. pneumophila to invade protozoa.